Beyond Greed and Fear / Understanding Behavioral Finance and the Psychology of Investing - Shefrin Hersh (Oxford University Press, 2002)
This book awakens us all to how little we know about financial markets, and how much we have to discover. Preface, What is Behavioral Finance?, Introduction, Heuristic-Driven Bias: The First Theme, Frame Dependence: The Second Theme, Inefficient Markets: The Third Theme, Prediction, Trying to Predict the Market, Sentimental Journey: The Illusion of Validity, Picking Stocks to Beat the Market, Biased Reactions to Earning Announcements, Individual Investors, ''Get-Evenitis'': Riding Losers Too Long, Portfolios and Pyramids and Emotions and Biases, Retirement Saving: Myopia and Self-Control, Institutional Investors, Open-Ended Mutual Funds: Misframing and ''Hot Hands'' and Obfuscation Games, Closed-End Funds: What Drives Discounts?, Fixed Income Securities: The Full Measure of Behavioral Phenomena, The Money Management Industry: Framing Effects and Style ''Diversification'' and Regret, The Interface between Corporate Finance and Investment, Corporate Takeovers and the Winner's Curse, Optimism in Analysts' Earnings Predictions and Stock Recommendations, Options and Futures and Foreign Exchange.